2014
DOI: 10.1021/ic501062r
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Enzyme Not Leach from Metal–Organic Frameworks (MOFs)? Unveiling the Interactions between an Enzyme Molecule and a MOF

Abstract: The strong interactions between microperoxidase (MP-11) and Tb-mesoMOF were identified via Raman spectroscopic studies, which revealed that MP-11 molecules interact with the framework of Tb-mesoMOF through π···π interactions between the heme of MP-11 and the conjugated triazine and benzene rings in the organic ligand of Tb-mesoMOF. The strong interactions facilitate the retention of MP-11 molecules within the metal-organic framework (MOF) pores, which is in striking contrast with the severe leaching of MP-11 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
119
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 22 publications
10
119
0
1
Order By: Relevance
“…22 mmol g À1 ) was almost double that with the adsorption method (ca. [38][39][40][41] Overall, covalent immobilization of biomolecules using COF 1 is superior to all the other tested porous materials (Figure 2). Inversely,t he leakage of lysozyme for the covalent method was far lower than that for the adsorption method ( Figure 2b).…”
mentioning
confidence: 92%
“…22 mmol g À1 ) was almost double that with the adsorption method (ca. [38][39][40][41] Overall, covalent immobilization of biomolecules using COF 1 is superior to all the other tested porous materials (Figure 2). Inversely,t he leakage of lysozyme for the covalent method was far lower than that for the adsorption method ( Figure 2b).…”
mentioning
confidence: 92%
“…In a previous report, Ma and coworkers have demonstrated the presence of π···π interactions between the immobilized enzyme and the conjugated ligands in a mesoporous cageMOF. 26 The HTB ligand in PCN-888 can form a large conjugated system between the heptazine core and terminal benzene rings, which should lead to a strong interaction with the immobilized enzymes. At the same time, the small window size of the cages also physically prevents the leaching of the enzymes from the framework, although the enzyme has to somehow make its way into the cage, one possible way being unfolding and refolding.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the small window size of the cages also physically prevents the leaching of the enzymes from the framework, although the enzyme has to somehow make its way into the cage, one possible way being unfolding and refolding. 26 In contrast, enzyme leaching of mesoporous silica materials, such as SBA-15, has proved to be significant even after one cycle, resulting in a severe reduction of the catalytic activity. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MOFs can exhibit strong hydrophobic interactions with immobilized enzymes that avert their leakage during operation. 39 Most importantly, MOFs enable the retention of enzyme activity upon harsh conditions that normally cause loss of the catalytic activity. 40 Our previous study focused on protein encapsulation mechanism in MOFs using molecular dynamic simulations also revealed that MOFs can function as a new category of host materials and molecular chaperones that support the protein folding and prevent their deactivations.…”
Section: Introductionmentioning
confidence: 99%